ANALYSIS OF PRIMATE DISTURBANCE IN COMMUNITY PLANTATIONS IN REREBE VILLAGE, TRIPE JAYA SUBDISTRICT, GAYO LUES REGENCY - Ali Makmur; Roslizawaty Roslizawaty; Anhar Haris; Syafruddin Syafruddin; Rasyida Ulfa; Herrialfian; Teuku Zahrial Helmi (VITEK : Bidang Kedokteran Hewan, 2026)
ABSTRACT. This study examines primate disturbances in community plantation areas in Rerebe Village, Tripe Jaya Subdistrict, Gayo Lues Regency. The research was conducted from November to December 2023 using observation and interview methods to identify the factors causing primate disturbances in community plantations, analyze the mitigation strategies employed by local communities, and identify primate species responsible for crop damage. Data were analyzed using a qualitative descriptive approach.The results revealed four primate species frequently disturbing community plantations: pig-tailed macaque (Macaca nemestrina), long-tailed macaque (Macaca fascicularis), Thomas’s langur (Presbytis thomasi), and slow loris (Nycticebus coucang). Primate disturbances primarily occurred when plantations were left unattended by farmers. Damage caused by pig-tailed macaques, long-tailed macaques, and Thomas’s langurs was similar, affecting chili, coffee, avocado, cocoa, banana, jackfruit, and durian crops. In contrast, slow lorises were observed to damage only coffee and cocoa plants. Mitigation measures applied by the community included the use of metal traps, rubber tires, zinc materials, shouting, throwing stones, lighting bonfires, and maintaining routine guarding of plantation areas.